Kesiapan Adopsi sebagai Mediator antara Kecemasan dan Perilaku Penggunaan Aplikasi FASIH pada Transformasi Digital Sensus dan Survei - Jati, Tristy Welas Ulas; Wibowo, S. Kunto Adi (Tuturlogi: Journal of Southeast Asian Communication, 2026)
In the digital era, the challenge of delivering census and survey results at a demanding speed has led BPS-Statistics to develop the Flexible Authentic Survey Instrument Harmony (FASIH) application as an integrated survey and census data collection system to enhance the effectiveness of digital data collection. Study related to the evaluation of the FASIH application has primarily focused on the technical aspects of technology; however, there has been no research from the perspective of application users. Using the UTAUT model, this study aims to investigate the role of adoption readiness as a mediator between user anxiety and usage behavior. Research Method is Using a quantitative approach with a sample of 185 employees in BPS-Statistics East Nusa Tenggara Province, which was taken by probability sampling. Data collection utilized an online form, with Partial Least Squares Structural Equation Modeling (PLS-SEM) employed for data analysis. Results of study is user anxiety has a negative and significant effect on adoption readiness. Furthermore, adoption readiness has a significant impact on usage behavior. Meanwhile, in the moderator variable of gender, there is no moderating effect of gender on the relationship between adoption readiness and usage behavior.